Circulating Tumor Cell Isolation: Efficient Purification and Release of Circulating Tumor Cells by Synergistic Effect of Biomarker and SiO2@Gel‐Microbead‐Based Size Difference Amplification (Adv. Healthcare Mater. 13/2016). Issue 13 (6th July 2016) - Huang, Qinqin; Cai, Bo; Chen, Bolei; Rao, Lang; He, Zhaobo; He, Rongxiang; Guo, Feng; Zhao, Libo; Kondamareddy, Kiran Kumar; Liu, Wei; Guo, Shishang; Zhao, Xing‐Zhong
Abstract : Efficient high‐purity recovery of viable circulating tumor cells (CTCs) allows the detection and characterization of cancer. On page 1554, W. Liu, S. S. Guo, X.‐Z. Zhao, and co‐workers describe a microfluidics‐based CTC‐isolation approach using CTC‐specific antibodies conjugated to silica microbeads. Continuous‐flow purification of CTCs is realized by laminar‐like interfaces. Based on a cell capture and release platform, viable cancer cells can be isolated from CTC blood samples. The low‐cost yet effective method is promising for point‐of‐care pharmacotherapy.